2019
DOI: 10.1093/crocol/otz009
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic Alterations Associated With Oral Delivery of Anti-CD3 (OKT3) Monoclonal Antibodies in Patients With Moderate-to-Severe Ulcerative Colitis

Abstract: Aim The aim of this study was to determine the immunologic effects and safety of oral anti-CD3 in patients with ulcerative colitis (UC). Methods An open-label pilot study of orally delivered anti-CD3 was performed in patients with moderate-to-severe UC. The primary end points were changes in immunologic parameters and evaluation for safety. Results Six subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
(33 reference statements)
0
10
0
Order By: Relevance
“…In the first study of six patients with moderate-to-severe ulcerative colitis who received oral anti-CD3 antibody, it was shown that it was well tolerated by all subjects. Nonetheless, it was not correlated with a change in Treg-associated molecule expression, namely Foxp3 and CTLA-4 ( 166 ). Currently, Foralumab (28F11-AE; NI-0401) is the only fully human anti-CD3 mAb ( 167 ).…”
Section: Role In Autoimmunitymentioning
confidence: 99%
“…In the first study of six patients with moderate-to-severe ulcerative colitis who received oral anti-CD3 antibody, it was shown that it was well tolerated by all subjects. Nonetheless, it was not correlated with a change in Treg-associated molecule expression, namely Foxp3 and CTLA-4 ( 166 ). Currently, Foralumab (28F11-AE; NI-0401) is the only fully human anti-CD3 mAb ( 167 ).…”
Section: Role In Autoimmunitymentioning
confidence: 99%
“…The biological mechanism of UC is the induction of regulatory T cells through anti-CD3 antibody uptake in gut-associated lymphoid tissue. Orally delivered muromonab-CD3 improved symptoms in the colon of patients with UC in a phase 2 trial using omeprazole, a proton pump inhibitor (NCT01287195) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a book on this subject, symptoms of anaphylaxis such as pyrexia (90 %; 40.0 °C or higher in 19 % of cases), chills (59 %), dyspnea (21 %), nausea and vomiting (19 %), chest pain (14 %), diarrhea (14 %), tremor (13 %), bronchospasm (13 %), headache (11 %), tachycardia (10 %), stiffness (8 %), and hypertension (8 %) were reported [148]. Pilot studies of this drug have been performed orally in patients with moderate to severe ulcerative colitis [149]. In this study, no severe side effects or CRS have been reported.…”
Section: Muromonabmentioning
confidence: 99%